The System of Claims Investigations by Consumer - Wróblewska, Karolina (Journal of Finance and Financial Law, 2016)
The system of claims investigations by consumer contains the most important information about consumer in financial sector. How consumer can complain about faulty services. What are the most important public institutions connected with consumer in financial sector. Which one of these institutions can solve given problem and what assignments they have and where they are. What documents consumer has to submit. How much time consumer has to wait for the end of this process. But all list of public institutions can help consumers.